Survival in Hostile Conditions: Pupylation and the Proteasome in Actinobacterial Stress Response Pathways - von Rosen, Tatjana; Keller, Lena ML; Weber-Ban, Eilika (Frontiers in Molecular Biosciences, 2021)
Bacteria employ a multitude of strategies to cope with the challenges they face in their natural surroundings, be it as pathogens, commensals or free-living species in rapidly changing environments like soil. Mycobacteria and other Actinobacteria acquired proteasomal genes and evolved a post-translational, ubiquitin-like modification pathway called pupylation to support their survival under rapidly changing conditions and under stress. The proteasomal 20S core particle (20S CP) interacts with ring-shaped activators like the hexameric ATPase Mpa that recruits pupylated substrates. The proteasomal subunits, Mpa and pupylation enzymes are encoded in the so-called Pup-proteasome system (PPS) gene locus. Genes in this locus become vital for bacteria to survive during periods of stress. In the successful human pathogen Mycobacterium tuberculosis, the 20S CP is essential for survival in host macrophages. Other members of the PPS and proteasomal interactors are crucial for cellular homeostasis, for example during the DNA damage response, iron and copper regulation, and heat shock. The multiple pathways that the proteasome is involved in during different stress responses suggest that the PPS plays a vital role in bacterial protein quality control and adaptation to diverse challenging environments.